On the Problems of Art with Originality Contexts, Dilemmas, Challenges - Solik, Ryszard (Cultural Arts Research and Development, 2025)
The sketch discusses selected contexts that are decisive for the narrative of the originality of art. These include historical, cultural, and discursive conditions. Hence the diachronic and culturological perspective of the analysis. This results from the confrontation between the past (tradition) and modernity, as well as from the conviction that culture and respected cultural premises determine the specificity of all phenomena and discourses. As a result, three issues are at the center of the text’s considerations: the context of a culture with low dynamics of change, the turning point of modernity, and the paradigmatic reorganizations of 20th-century art and the problems (challenges) associated with them. The first element is related to the discourse on the originality of art in a culture oriented toward the past. The second marks the breakthrough of modernity, which, in the name of Enlightenment progress, change, and modernization of the world, redefines the concept of originality, while unleashing the extraordinary capacity of art for transformation and artistic innovation. Within the artistic transgressions of modern art, the background for reflections on the originality of art is set by the multi paradigmatic nature of art. This is fundamentally linked to radical and comprehensive transformations in the ontological nature of the work of art (the diversity of art: from the object to the process and event of participatory and interactive art). The originality of art is understood in the text as a dynamic and contextual problem, constructed ad hoc and resulting from many variables.